Economic and geopolitical dimensions of renewable vs. nuclear energy in North Africa - Marktanner, Marcus; Salman, Lana (Energy policy, 2011)
Addressing issues of renewable energy in North Africa must incorporate concerns regarding the compatibility of energy mixes with the nature of political regimes, their geopolitical relevance, and their socio-economic effects, in addition to economic cost-benefit deliberations. One important and under-researched aspect of nuclear energy refers to the trade-off between socio-economic development and political power conservation. Competing interests in North Africa's energy market as well as aspects of regional cooperation capacity are important when assessing the choice between renewable and nuclear energy. Therefore, the future course of meeting North Africa's energy needs is subject to a complex political and economic interplay between domestic and geopolitical development interests. The objective of this paper is to explore this complexity in more detail. We argue that the identification of any energy alternative as superior is hardly convincing unless certain standards of inclusive governance are met. We also find that it is important to highlight political–economic differences between energy importers like Morocco and Tunisia and energy exporters like Algeria, Libya, and Egypt. ► North Africa confronted with severe energy supply challenges in near future. ► Trade-off between socio-economic development and political power conservation matters. ► Economic and geopolitical dimensions of trade-off heterogeneous across North Africa.